Hepatic expression and serum levels of syndecan 1 (CD 138) in patients with nonalcoholic fatty liver disease - ÇELİKEL, ÇİĞDEM; EREN, FATİH; YILMAZ, YUSUF (INFORMA HEALTHCARE, 2012)
Background and aims. Syndecan-1 (CD 138) is a transmembrane heparan sulfate proteoglycan expressed in the liver which may exert metabolic effects by mediating the hepatic clearance of triglyceride-rich lipoproteins. In the present study, we assayed serum levels and the hepatic expression of syndecan-1 and examined their association with clinical, biochemical, and histologic phenotypes in patients with histology-proven nonalcoholic fatty liver disease (NAFLD). Methods. A total of 59 patients with biopsy-proven NAFLD and 54 matched controls were enrolled. The analysis of syndecan-1 expression in liver biopsies was performed by immunohistochemistry on formalin-fixed, paraffin-embedded samples. Serum syndecan-1 levels were measured by ELISA. Results. NAFLD patients had significantly higher serum syndecan-1 levels [median: 61 ng/mL (interquartile range: 36-97 ng/mL)] than controls [median: 37 ng/mL (interquartile range: 25-59 ng/mL, Mann Whitney U test, p < 0.001]. However, we did not find any significant association between serum syndecan-1 and the mean syndecan-1 immunohistochemical score (n = 59, r = 0.064, p = 0.63). Interestingly, the syndecan-1 immunohistochemical score was an independent predictor of HDL cholesterol in NAFLD patients (beta = 0.27; t = 1.99, p < 0.05). Conclusions. Our data suggest that serum syndecan-1 levels are raised in patients with NAFLD. Moreover, the syndecan-1 immunohistochemical score in the liver is independently associated with HDL cholesterol in this group of patients. These pilot results support further investigation of this molecule in metabolic liver diseases.
Keywords: enzyme-linked immunosorbent assay; immunohistochemistry; nonalcoholic fatty liver disease; syndecan-1; METABOLIC SYNDROME; HEPARAN-SULFATE; ASSOCIATION; STEATOSIS; DIAGNOSIS; FIBROSIS; CANCER; STEATOHEPATITIS; CLEARANCE; CARCINOMA